Apple Pro Training Series : DVD Studio Pro 4 - Sitter, Martin; Ramseier, Adrian (Peachpit Press, 2005)
Now the best-selling book on DVD Studio Pro is even better. Fully updated for DVD Studio Pro 4 and with complete coverage of the new version of Compressor, the industrial-strength encoder that dramatically speeds up encoding of MPEG-2 and H.264 HD DVD video, this self-paced guide is the fastest way to learn to author professional, interactive DVDs. Master trainers Martin Sitter and Adrian Ramseier begin with the basics of DVD authoring and take you all the way through DVD Studio Pro's powerful advanced features. Each chapter presents a complete lesson on an aspect of DVD creation, with hands-on projects for you to complete as you go. All the files are included on the accompanying DVD. After learning how to storyboard a DVD and plan its interactions, you'll set chapter markers, build still, layered, and motion menus, and add subtitles and Web links. You'll also learn sophisticated techniques for juggling multiple audio tracks and camera angles, creating custom transitions, building advanced overlays, and scripting. By the end of the book, you'll have created four full DVDs. The Apple Pro Training Series is both a self-paced learning tool and the official curriculum of the Apple Pro Training and Certification Program. Upon completing the course material in this book, you can become a certified Apple Pro b taking the certification exam at an Apple Authorized Training Center. To find an Authorized Training Center near you, go to www.apple.com/software/pro/training.